Rice Selling Vs. Grain Selling Farms: Which One is More Profitable? - Adi Nurfadilah Rosyandi; Supadi Supadi; Kikin Windhani (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2019)
The objectives of this study were to compare the income and efficiency between grain selling farmers and rice selling farmers, and analyzed added value. Population in this study were all rice farmers in Kapandayan Village. With proportionate random sampling, 34 grain selling farmers and 16 rice selling farmers were selected as respondents. The data were analyzed with income analysis, independent samples t-test, Hayami’s method and R/C ratio. The results indicated that rice selling farmers had a higher income than grain selling farmers, the result of t test indicated that there was a significant difference. Hayami’s method indicated that there was a positive added value of Rp786/kg, from which the farmers received 86% of total added value, and the remaining 14% was received by direct labor. R/C ratio of grain selling farmers was 1.57 and R/C ratio of rice selling farmers was 1.68. The analysis result of R/C ratio indicated that rice farmers in Kapandayan Village have been efficient.Keywords: Farmer, Income, Value Added, Efficiency.